Maturation of mismatch negativity: a scalp current density analysis - Martin, Brett A; Shafer, Valerie L; Morr, Mara L; Kreuzer, Judith A; Kurtzberg, Diane (Ear and hearing, 2003)
Auditory evoked potentials provide the opportunity to better understand the central processing of auditory stimuli, which is the basis of speech and language perception. The purpose of this study was to examine maturational changes in the topography of one of these auditory evoked potentials, the mismatch negativity (MMN), using scalp current density (SCD) analysis. Subjects were children ages 4 to 11 yr (N = 53), and adults (N = 12). Stimuli were 85 dB peSPL 1000 Hz standard tones and 1200 Hz deviant tones (deviant probability = 0.15). Auditory evoked potentials were recorded using surface electrodes placed at 32 locations on the head while subjects ignored the stimuli by watching a silent video. Significant maturational changes in topography of MMN were seen over frontal and left lateral sites. Differences in MMN for the children compared to adults indicate that the MMN generators or their orientation, and thus the neural processes underlying discrimination of simple tones, are not yet mature by 11 yr of age.